Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $|a|<1$ then $\lim_{n \to \infty} a^n=0 $

I used to prove it by taking the logarithm but now saw a different solution in the book:

Consider the sequence $b_n = |a|^n$ , $b_{n+1}=b_n \cdot |a|$ < $b_n$ which means that $b_n$ is decreasing.

$b_1>b_2>....>b_n>0$ converges

Assume that $b_n$→$l$ , $b_{n+1} = |a| \cdot b_n$

Then, $b_{n+1} \to l$ and $b_n \to l \implies l=|a| \cdot l \implies l(1-|a|)=0 \implies l = 0$ as $1-|a|\neq0$.

I could not understand how he could write $b_{n+1} \to l$. Could you please explain it to me? Can we always make an assumption that if a series $c_n$ converges to $m$ then $c_{n+m}$, $m\in\mathbb N$ also converges to $m$ or $c_{n-1}$ also converges to $m$?

share|cite|improve this question
$\sum a^n = 1 / (1-a)$. On the other hand $\lim a^n =0$. – Nikita Evseev Dec 5 '12 at 3:36
@nikita2 you are right. I edited my question. – Amadeus Bachmann Dec 5 '12 at 3:38
up vote 1 down vote accepted

Well, since we're letting the parameter $n$ get arbitrarily large, there's no difference in saying $n$, $n+1$, $n+m$ for some $m > 0$, or even saying $2n$, $3n$, etc.

The reasoning behind this is that the only thing we care about when dealing with the limit of a sequence is how it behaves asymptotically i.e. when $n$ is very large.

A bit more rigor. A sequence $\{a_n\}_{n \in \mathbb{N}}$ approaches a finite limit $l$ if for any $\varepsilon > 0$ there exists $N = N(\varepsilon) \in \mathbb{N}$ such that for any $n > N$, $|a_n-l|<\varepsilon$. Now suppose $a_n \to l$, and let $b_n = a_{n + m}$. Let $\varepsilon > 0$ be given, and we know that $|a_n - l| < \varepsilon$ for any $n > N = N(\varepsilon)$. Now, we know that $n+m > n > N$, so $|b_n - l | = |a_{n+m} - l|<\varepsilon$, so $b_n \to l$ as well.

To answer your second question, will this work if $m$ is negative? Yes, if $a_n \to l$ and $b_n = a_{n+m}$, then $b_n \to l$ as well. Take $N_b$ to be equal to $N_a + m$, and the condition is satisfied.

share|cite|improve this answer

If I understand your question, to say $c_{n} \rightarrow a$ is to say that for every $\epsilon>0$, there exists an $N$ so that for every $n>N$, $|c_{n}-a|<\epsilon$. To say that $c_{n+1} \rightarrow a$ is to say that for every $\epsilon>0$ there exists an $M$ so that for every $n+1>M$, $|c_{n+1}-a|<\epsilon$. Can you see how the two statements are equivalent?

share|cite|improve this answer
yeah it is so simple. how could not I think that! :/ I guess I need to take a rest. thank you for your answer. – Amadeus Bachmann Dec 5 '12 at 3:55

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.